Living class in John Updike's "A&P". Issue 2 (2nd April 2020) - Aguiar, Christian
Abstract: This article uses Beverly Skeggs' notion of "living class" to explore the ways class perception – and misperception – influences the narrative in John Updike's short story "A&P." It suggests that the narrator, whose actions are often viewed as rebellious, has actually misunderstood his own class position due to the deceptive class dynamics of the supermarket where he works.